Interoperability and HealthGRID - Bescos, C.; Schmitt, D.; Kass, J.; García-Barbero, M.; Kantchev, P. (Methods of Information in Medicine, 2005)
Objectives: GRID technology, with initiatives like the GGF, will have the potential to allow both competition and interoperability not only among applications and toolkits, but also among implementations of key services.The pyramid of eHealth interoperability should be achieved from standards in communication and data security, storage and processing, to the policy initiatives, including organizational protocols, financing procedures, and legal framework.The open challenges for GRID use in clinical fields illustrate the potential of the combination of grid technologies with medical routine into a wider inter-operable framework.Methods: The Telemedicine Alliance is a consortium (ESA, WHO and ITU), initiated in 2002, in building a vision for the provision of eHealth to European citizens by 2010. After a survey with more that 50 interviews of experts, interoperability was identified as the main showstopper to eHealth implementation.Results: There are already several groups and organizations contributing to standardization. TM-Alliance is supporting the “e-Health Standardization Coordination Group” (eHSCG).Conclusions: It is now, in the design and development phase of GRID technology in Health, the right moment to act with the aim of achieving an interoperable and open framework. The Health area should benefit from the initiatives started at the GGF in terms of global architecture and services definitions, as well as from the security and other web services applications developed under the Internet umbrella. There is a risk that existing important results of the standardization efforts in this area are not taken up simply because they are not always known.
Keywords: Healthgrid; interoperability; standards; Telemedicine Alliance; ESA; WHO; ITU